The Challenges of Globalization and the Response to the Renewal of Islamic Thought - Moliza; Shofiullah Muzammil (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Globalization is a complex phenomenon encompassing economic, social, cultural, and political integration between countries worldwide. While offering numerous opportunities, globalization also presents significant challenges that require in-depth understanding and a careful approach. The challenges of globalization have impacted various aspects of life, including the context of Islamic thought. Globalization brings about major changes in the economy, culture, and technology, often challenging the preservation of religious values ​​and teachings. Globalization is an unstoppable phenomenon emerging through rapid technological advancements resulting in hyperconnectivity, with digitalization and the metaverse quickly defining our reality.